The impact of stock market manipulation on Nigeria's economic performance - Babatunde Akinmade; Festus Fatai Adedoyin; Festus Victor Bekun (Journal of Economic Structures, 2020)
This study is the first attempt to empirically analyse stock market manipulation on the Nigerian Stock Exchange and its consequences on economic performance. The empirical investigation employs a broad data set of 186 actual manipulation cases indicted by the Nigerian Security and Exchange Commission between 2002 and 2016. We embrace market microstructure analysis and the event study method to understand how various manipulation techniques impact on market measures, and the Error Correction Model to evaluate their economic effects. Manipulation is found to distort market efficiency measures (such as market capitalization, value traded ratio and All-Share Index) and genuine traders are forced to exit the market to avoid possible trading with a manipulator. Such huge divestment and the subsequent financial risk weaken the ability of the Stock Exchange market to improve economic performance, creating negative consequences at the post-manipulation period. Essentially, eco-nomic variables (such as the GDP) react negatively to manipulative trading. This finding is insightful and a prompt to the Securities and Exchange Commission to design policy responses towards deterring and prosecuting unfair trading practices or other activities that contravene the market rules.
Keywords: 330; Nigerian Stock Exchange; Market manipulation; Market microstructure; Event study; Market efficiency measures; Market indicators; Economic growth